Exploring functional metabolites and proteomics biomarkers in late-preterm and natural-born pigs - Chong, Jie; Wang, Juan; Zhong, Hang; Zhang, Jinwei; Ding, Yuchun; Ge, Liangpeng; Ma, Jideng; Sun, Jing (Frontiers in Veterinary Science, 2024)
Pigs are often used to study the intestinal development of newborns, particularly as preterm pig models that mimic the intestinal growth of human preterm infants.Neonatology's study of delivery mode's impact on neonatal development is crucial, therefore, we established 14 newborn pigs delivered via cesarean sections (C-sections, at 113 days of gestational age, CS group) and 8 naturally born pigs were used as controls (at 114 days of gestational age, NF group). The impact of two alternative delivery procedures (C-sections and natural birth) on the levels of short-chain fatty acids (SCFAs) and organic acids in the hepatic and intestines of newborn pigs were compared using metabolomics. The underlying molecular pathways are examined at the "proteinmetabolite" level by integrating proteomic data. The findings demonstrated that the mode of delivery changed the metabolism of SCFAs in newborn pigs, perhaps by affecting the physiology levels of cyclic intermediates such as lactate and malate in the pyruvate metabolic pathway. Additionally, by participating taking part in the fatty acid metabolism pathway, two distinct proteins (FASN and HSD17B4) may impact the physiological concentration of these tiny metabolites. In conclusion, this study provided reliable animal model data for understanding the physiological SCFAs metabolic information and its affecting mechanism of large-gestational age preterm infants.